2015
DOI: 10.1097/med.0000000000000155
|View full text |Cite
|
Sign up to set email alerts
|

Actin binding proteins in blood–testis barrier function

Abstract: Purpose of review This review examines the role of actin binding proteins (ABPs) on blood-testis barrier (BTB), an androgen-dependent ultrastructure in the testis, in particular their involvement on BTB remodeling during spermatogenesis. Recent findings The BTB divides the seminiferous epithelium into the basal and the adluminal compartments. The BTB is constituted by coexisting actin-based tight junction (TJ), basal ectoplasmic specialization (ES) and gap junction (GJ), as well as intermediate filament-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 100 publications
1
9
0
Order By: Relevance
“…Herein we discuss some recent findings based on studies of the following selected actin-binding/regulatory proteins in the testis and how these proteins work alone or in concert with others to modulate the organization of actin microfilaments, most notably at the ES to regulate (1) spermatid adhesion and transport and (2) BTB dynamics to facilitate the transport of preleptotene spermatocytes across the immunological barrier. Other regulatory proteins such as actin-bundling proteins plastin 3, Eps8, ezrin, and palladin and regulatory protein kinases (e.g., FAK, c-Src, c-Yes) pertinent to the regulation of spermatogenesis have recently been reviewed [14, 19], and thus, they are not being discussed herein to avoid redundancy. Instead, we focus on a group of actin nucleation proteins; however, these actin nucleation proteins are grouped into two types: one confers branched actin nucleation (e.g., the Arp2/3 complex), whereas the other type confers linear actin nucleation (e.g., formin 1 and Spire 1).…”
Section: Actin-based Cytoskeletonmentioning
confidence: 99%
See 2 more Smart Citations
“…Herein we discuss some recent findings based on studies of the following selected actin-binding/regulatory proteins in the testis and how these proteins work alone or in concert with others to modulate the organization of actin microfilaments, most notably at the ES to regulate (1) spermatid adhesion and transport and (2) BTB dynamics to facilitate the transport of preleptotene spermatocytes across the immunological barrier. Other regulatory proteins such as actin-bundling proteins plastin 3, Eps8, ezrin, and palladin and regulatory protein kinases (e.g., FAK, c-Src, c-Yes) pertinent to the regulation of spermatogenesis have recently been reviewed [14, 19], and thus, they are not being discussed herein to avoid redundancy. Instead, we focus on a group of actin nucleation proteins; however, these actin nucleation proteins are grouped into two types: one confers branched actin nucleation (e.g., the Arp2/3 complex), whereas the other type confers linear actin nucleation (e.g., formin 1 and Spire 1).…”
Section: Actin-based Cytoskeletonmentioning
confidence: 99%
“…However, these two cytoskeletal networks are intimately associated structurally and functionally to support spermatogenesis [9, 19]. Interestingly, studies have shown that both cytoskeletal networks can be modulated by the same proteins.…”
Section: Mt-based Cytoskeletonmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, those located at the Sertoli-Sertoli cell interface are referred to as the basal ES, which usually coexists with tight junctions and gap junctions to constitute the BTB structure. Interestingly, germ cell transport as well as endocytic vesicle trafficking in Sertoli cells requires rapid reorganization of these microfilament bundles, so that they are efficiently converted from a “bundled” to “unbundled/branched” configuration (Li et al, 2015). Briefly, there is no doubt that irrespective of the type of actin bundle configuration, in all cases they support and maintain cell junction integrity.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins coordinate to regulate actin microfilament remodeling at the basal ES and apical ES via their stage-specific and spatiotemporal expression, which, in turn, facilitate the transport of preleptotene spermatocytes across the BTB and the transport of elongating spermatids across the adluminal compartment, respectively. The coordinated efforts of those actin regulatory proteins have recently been reviewed (Li et al 2015a; Cheng and Mruk 2015; Su et al 2013). Herein, we focus our discussion on drebrin, a family of proteins known to regulate the action of the Arp2/3 complex which is a barbed end nucleation protein that effectively induces branched actin polymerization, thereby converting actin microfilaments from a linear to a branched configuration.…”
Section: 2 Actin Cytoskeleton Ectoplasmic Specialization (Es) Anmentioning
confidence: 99%